Rethinking Sustainable Development Goals (SDGs) among Karen “Longneck” Women Hill Tribe in Northern Thailand - Dania, Maya (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2020)
The Karen tribe, originating from a branch within the Burmese Kayan ethnic group, now comprises the most considerable portion of Thailand's ethnic highland population. The tribe has been migrating throughout Thai-Myanmar mountainous border, as the impact of armed conflict between Karen nationalist and Burmese government since the 1950s and as democracy faltered in Myanmar. In the last two decades, the number of Karen people who migrated to Chiang Rai has been increasing due to the new industry of tribal tourism in the province. However, for Thai people, the hill tribe people are still considered alien or the other, but their presence must be integrated into Thai society. Therefore, the Thai government issued a special identity card for the hill tribes identifying them as people belonging to ethnic minorities, yet, non-Thai citizens. There are currently three categories to recognize hill tribe people in Thailand based on the Cabinet resolutions and laws passed to reflect the level of the state's acceptance of the citizenship status. However, this policy brings contradictive sense, especially in terms of citizenship rights and fulfilling SDGs for the hill tribes. This research focuses on Karen